Utilisation of biodegradable solid waste to boost crop production among farmers in Mbarara city, south western Uganda - Twesigye, Naboth; Twinamatsiko, Medard; Tumwesigye, Wycliffe (American Journal of Agriculture, 2022)
Purpose: Determining the utilisation of biodegradable solid waste in boosting crop productivity among farmers in Mbarara City. Methodology: Mixed methods were used with simple random sampling and purposive sampling to obtain 111 and 31 respondents respectively -altogether constituting 142 respondents. Data was collected from the respondents using a questionnaire and an interview guide. The study adopted both descriptive and correlational data analysis. Findings: The study identified some practices that were used in managing biodegradable solid waste for application in boosting crop productivity among farmers in Mbarara city. These were communal collection, door-to-door collection, and others like roadside dumping and dustbins. The application of biodegradable solid waste in boosting crop productivity among farmers of Mbarara city was found to be relatively low, notwithstanding the fact that for those who applied the biodegradable solid waste in farming, it increased crops yields. The study further identified compositing of biodegradable solid waste as the main innovative strategy for proper utilization of solid wastes towards crop productivity. This was because the strategy is environmentally friendly at the same time it enriches the soil with both soil and crop growth support nutrients. Unique contribution to theory, practice and policy: A strong cooperation between the community and the city council authorities should be cultivated for purposes of enhancing community participation in the management of biodegradable solid waste hence enhancing food crop production in the area. There is also need to explore the opportunities of reducing, reusing, recycling and rethinking and composting in waste management among urban communities to minimize waste and increase economic benefits. Successfully adoption of sustainable methods of waste management by the communities can be done by making awareness programmes simple and accessible to change the mind-set of urban residents to perceive waste as resources rather a problem.
Keywords: Solid waste; Biodegradable; Utilization of biodegradable solid waste; Crop productivity.